2017
DOI: 10.4172/2380-2391.1000222
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Potentially Toxic Metals (PTMs) from Two Nigerian Clays and Related Clay Pottery Used Locally as Foodwares

Abstract: There is presently lack of data on composition of potentially toxic metals and their leaching from clay based foodwares into food. Therefore, in present study we evaluated the leaching of cadmium, chromium, copper, manganese, nickel, lead and zinc from raw clays and traditional clay pots from two locations, Ara-Ekiti, Ekiti State and Kono-Boue, Rivers State in Nigeria. Samples were digested with aqua regia and analysed using atomic absorption spectrometry and also with energy dispersive X-ray fluorescence. Tap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Aleksanyan et al, [32] reported the tendency of Fe to leach at near neutral to neutral pH conditions. The Concentration of Zn was higher at pH 5 than at pH 7, this varying trend in concentration of Zn leached at the different pH conditions was also recorded by Boisa et al [31]. Pb was not detected at all pH conditions.…”
Section: Effect Of Ph On the Amount Of Ptms Leached From Castsupporting
confidence: 79%
See 2 more Smart Citations
“…Aleksanyan et al, [32] reported the tendency of Fe to leach at near neutral to neutral pH conditions. The Concentration of Zn was higher at pH 5 than at pH 7, this varying trend in concentration of Zn leached at the different pH conditions was also recorded by Boisa et al [31]. Pb was not detected at all pH conditions.…”
Section: Effect Of Ph On the Amount Of Ptms Leached From Castsupporting
confidence: 79%
“…The concentration of Fe gradually increased from pH 3 to 5 and at pH 6 it decreased and increased at pH 7. Boisa et al, [31] observed that the concentration of Fe leached upon exposure of Ara-Ekiti clay pot to water of Acidic pH, Neutral pH, alkaline pH were (1.15 mg/L 0.16 mg/L, and 0.08 mg/L respectively). Aleksanyan et al, [32] reported the tendency of Fe to leach at near neutral to neutral pH conditions.…”
Section: Effect Of Ph On the Amount Of Ptms Leached From Castmentioning
confidence: 99%
See 1 more Smart Citation